2021
DOI: 10.21203/rs.3.rs-741834/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary Game Analysis on Behavioral Strategies of Multiple Stakeholders in Inclusive Green Growth

Abstract: Inclusive green growth has been set as an important initiative to solve the severe problems of environmental degradation and severe income inequality. It requires the joint participation of local government, enterprise and public. However, these stakeholders are not enthusiasm enough as there are divergences among their interest goals. Hence, this paper analyses how to balance the stakeholders’ interest goals based on the central supervision and local regulation in environmental protection and income inequity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Cao et al ( 16) and Encarnacao et al (17) constructed a three-subject evolutionary game model involving the government, enterprise, and the public to investigate the public's role mechanism in green technology innovation. Qu et al (18) and Guan et al (19) studied the evolution strategies of the government, the public, and the enterprise and discovered that they are not only related to the initial participation ratio of each subject but also affected by the value of their related parameters. A small number of scholars have found that the behaviors of green organizations, scientific research institutions, and financial institutions will also have an impact on the enterprise's green technology innovation strategy (20)(21)(22).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cao et al ( 16) and Encarnacao et al (17) constructed a three-subject evolutionary game model involving the government, enterprise, and the public to investigate the public's role mechanism in green technology innovation. Qu et al (18) and Guan et al (19) studied the evolution strategies of the government, the public, and the enterprise and discovered that they are not only related to the initial participation ratio of each subject but also affected by the value of their related parameters. A small number of scholars have found that the behaviors of green organizations, scientific research institutions, and financial institutions will also have an impact on the enterprise's green technology innovation strategy (20)(21)(22).…”
Section: Literature Reviewmentioning
confidence: 99%